A waste to wealth approach through utilization of nano-ceramic tile waste as an accessible and inexpensive solid support to produce a heterogeneous solid acid nanocatalyst: to kill three birds with one stone. Issue 96 (3rd October 2016) - Kolvari, Eskandar; Zolfagharinia, Somayeh
Abstract : Waste minimization through the utilization of cost-effective, available, and nontoxic nano-ceramic tile wastes for the heterogenization of sulfuric acid. Abstract : Regarding the subject of waste products/materials, recycling or reusing has had a pivotal role on account of environmental and economic reasons. As a consequence, the essential task, nowadays, can be invention of new and practical pathways to reuse or even recycle them. In this framework, until now, recycling of some waste products such as tile wastes has not been taken into consideration; so, we were prompted by the possibility of recycling tile wastes in the catalytic direction. To this end, we use them as cost-effective, available, and nontoxic support materials for the heterogenization of sulfuric acid, in order to prepare the novel nano-ceramic tile waste supported sulfonic acid catalyst (nano-ceramic tile waste-SO3 H or n-CTW-SA). This solid acid catalyst was well characterized through FT-IR, XRD, FE-SEM, EDX, TEM, TGA, BET, BJH, pH analysis and Hammett acidity function. The as-prepared nano-ceramic tile waste supported sulfonic acid catalyst proved to be an active heterogeneous catalyst in multicomponent reactions (MRCs) for the rapid and efficient one-pot synthesis of 2, 4, 5-trisubstituted and 1, 2, 4, 5-tetrasubstituted imidazoles in high yields and selectivity. In comparison with some other homogeneous and heterogeneous catalysts, nano-ceramic tile waste supported sulfonic acid displayed a greater activity. Moreover, being highly stable, inexpensive, accessible, retrievable, reusable, and having low toxicity are some other beneficial points of this catalyst.